DIKSI DAN GAYA BAHASA IKLAN PRODUK KECANTIKAN DALAM BEAUTY GUIDE ORIFLAME - Deviana Ameliyah; Mutiah, Arju; Purnomo, Bambang Edi (TOTOBUANG, 2024)
Abstract Beauty Guide Oriflame is an advertising media that presents various kinds of beauty advertisements from Oriflame products. This research discusses various kinds of diction and language styles used in Oriflame beauty product advertisements. The purpose of this study is to describe the diction and language style of beauty product advertisements in Beauty Guide Oriflame. This research is a qualitative research with interpretative descriptive data analysis technique. The data in this study are words, phrases, and sentences that indicate the use of diction and language style in beauty product advertisements. The data source is beauty product advertisements published in the January - February 2022 edition of Beauty Guide Oriflame. The data collection technique in this study used documentation technique. The results show that (1) diction in beauty product advertisements includes diction in the form of 2 data of denotative words, 2 data of connotative words, 3 data of general words, 3 data of special words, and 2 data of popular words and (2) language styles in beauty product advertisements include 2 data of language style simile, 5 data of personification, 4 data of hyperbole, 1 data of litotes, 1 data of metonimia, 4 data of hypothesis, 2 data of polysidenton, 1 data of alliteration, 2 data of anaphora, and 1 data of epistrofa. The use of diction and language style is important in an advertisement for Oriflame beauty products because it aims to attract the attention of readers or potential consumers in providing information related to the products needed, and can build a positive image of the products offered. Keywords: diction, language style, advertisement, Beauty Guide Oriflame.   Abstrak Beauty Guide Oriflame merupakan suatu media iklan yang didalamnya menyajikan berbagai macam iklan kecantikan dari produk Oriflame. Penelitian ini membahas berbagai macam diksi dan gaya bahasa yang digunakan dalam iklan produk kecantikan Oriflame. Tujuan penelitian ini adalah untuk mendeskripsikan diksi dan gaya bahasa iklan produk kecantikan dalam Beauty Guide Oriflame. Penelitian ini merupakan penelitian kualitatif dengan teknik analisis data deskriptif interpretatif. Data dalam penelitian ini berupa kata, frasa, dan kalimat yang mengindikasikan adanya penggunaan diksi dan gaya bahasa pada iklan produk kecantikan. Sumber data penelitian adalah iklan produk kecantikan yang dimuat dalam Beauty Guide Oriflame edisi Januari - Februari 2022. Teknik pengumpulan data dalam penelitian ini menggunakan teknik dokumentasi. Hasil penelitian menunjukkan bahwa terdapat (1) diksi dalam iklan produk kecantikan meliputi diksi yang berupa 2 data kata denotatif, 2 data kata konotatif, 3 data kata umum, 3 data kata khusus, dan 2 data kata populer dan (2) gaya bahasa dalam iklan produk kecantikan meliputi 2 data gaya bahasa perumpamaan (simile), 5 data personifikasi, 4 data hiperbola, 1 data litotes, 1 data metonimia, 4 data erotesis, 2 data polisidenton, 1 data aliterasi, 2 data anafora, dan 1 data epistrofa. Penggunaan diksi dan gaya bahasa penting dalam sebuah iklan produk kecantikan Oriflame sebab bertujuan untuk menarik perhatian pembaca atau calon konsumen dalam memberikan informasi-informasi terkait produk yang dibutuhkan, dan dapat membangun citra positif dari produk yang ditawarkan. Kata-kata kunci: diksi, gaya bahasa, iklan, Beauty Guide Oriflame.